Alkaline electrolyzed water AS a potential green degreaser for meat processing stainless steel surface - Khalid, Nurul Izzah; Ab Aziz, Norashikin; Noh, Teh Ubaidah; Abd Rahim, Muhamad Hafiz (John Wiley and Sons, 2023)
The meat industry faces significant challenges regarding removing fat, oil, and grease (FOG) residues from meat processing stainless steel surfaces, compounded by limited resources and inadequate cleaning knowledge. As an innovative solution to these difficulties, alkaline electrolyzed water (AlEW), a sustainable green degreaser, is proposed to replace the traditional alkaline wash. AlEW is produced through two“chamber (membrane) electrolysis at the cathode. AlEW with a strong reducing potential (ˆ’800 to ˆ’900 mV), high pH (10.0“11.5), and high dissolved oxygen are used to remove FOG residues from meat processing stainless steel surfaces. Our comprehensive analysis highlights the advantages of AlEW as a sustainable alternative to conventional degreasers for the meat industry, including ease of use, no storage requirements, and reduced costs for wastewater treatment. Our findings underscore AlEW's potential to improve the meat industry's quality, safety, and environmental sustainability. This review contributes to ongoing discussions about sustainable food industry solutions, aligning with the 2030 Agenda for Sustainable Development goals. In conclusion, AlEW is a promising alternative to conventional degreasers, advancing sustainability in the meat industry.